Intorno a Boccaccio / Boccaccio e dintorni 2019 Atti del Seminario internazionale di studi (Certaldo Alta, Casa di Giovanni Boccaccio, 12-13 settembre 2019) - Frosini, Giovanna (Studi e saggi, 2020)
The volume Intorno a Boccaccio / Boccaccio e dintorni 2019 was born from the international study seminar that took place in Certaldo Alta, in the House of Giovanni Boccaccio, on 12 and 13 September 2019. The Seminar, now in its sixth edition, is proposed as one of the most solid and significant appointments in the activity of the Giovanni Boccaccio National Organization, and as one of the events that best characterizes its mission. Created to give a voice particularly to young scholars, over the years it has become an important appointment for presenting and discussing research in progress or just concluded, and always open to future developments. With this volume, which includes essays particularly focused on philological, literary, historical-linguistic and lexicographic aspects, a series led by an authoritative Scientific Committee is inaugurated.